Answer:
the answer is 2x+2
Step-by-step explanation:
you have to distribute the two equations and add the common factors together.
Answer:
<h2>
y = -4/9</h2>
Step-by-step explanation:
Given the system of equations y = 3/2 x − 6, y = −9/2 x + 21, since both expressions are functions of y, we will equate both of them to find the variable x;
3/2 x − 6 = −9/2 x + 21,
Cross multiplying;
3(2x+21) = -9(2x-6)
6x+63 = -18x+54
collecting the like terms;
6x+18x = 54-63
24x = -9
x = -9/24
x = -3/8
To get the value of y, we will substitute x = -3/8 into any of the given equation. Using the first equation;
y = 3/2x-6
y = 3/{2(-3/8)-6}
y = 3/{(-3/4-6)}
y = 3/{(-3-24)/4}
y = 3/(-27/4)
y = 3 * -4/27
y = -4/9
Hence, the value of y is -4/9
Answer:
i think ii first add 5x + x then you can remove the parentheses, group similar terms and add similar elements
Step-by-step explanation:
A function assigns the values. The function of the graph g(x) is 3(2ˣ).
<h3>What is a Function?</h3>
A function assigns the value of each element of one set to the other specific element of another set.
Given the function of the graph is f(x)=3(2ˣ)-3, which is needed to be transformed to g(x), since g(x) is the function of f(x) transformed 3 units upwards therefore, the function of g(x) can be written as,
g(x) = f(x) + 3
g(x) = 3(2ˣ)-3+3
g(x) = 3(2ˣ)
Hence, the function of the graph g(x) is 3(2ˣ).
Learn more about Function:
brainly.com/question/5245372
#SPJ1